A new photometric and dynamical study of the eclipsing binary star HW Virginis. Issue 2 (2nd July 2021) - Brown-Sevilla, S B; Nascimbeni, V; Borsato, L; Tartaglia, L; Nardiello, D; Granata, V; Libralato, M; Damasso, M; Piotto, G; Pollacco, D; West, R G; Colombo, L S; et al.
ABSTRACT: A growing number of eclipsing binary systems of the 'HW Virginis' (HW Vir) kind (i.e. composed by a subdwarf-B/O primary star and an M dwarf secondary) show variations in their orbital period, also called eclipse time variations (ETVs). Their physical origin is not yet known with certainty: While some ETVs have been claimed to arise from dynamical perturbations due to the presence of circumbinary planetary companions, other authors suggest that the Applegate effect or other unknown stellar mechanisms could be responsible for them. In this work, we present 28 unpublished high-precision light curves of one of the most controversial of these systems, the prototype HW Vir. We homogeneously analysed the new eclipse timings together with historical data obtained between 1983 and 2012, demonstrating that the planetary models previously claimed do not fit the new photometric data, besides being dynamically unstable. In an effort to find a new model able to fit all the available data, we developed a new approach based on a global-search genetic algorithm and eventually found two new distinct families of solutions that fit the observed timings very well, yet dynamically unstable at the 10 5 -yr time-scale. This serves as a cautionary tale on the existence of formal solutions that apparently explain ETVs but are not physically meaningful, and on the need of carefully testing their stability. On the other hand, our data confirm the presence of an ETV on HW Vir that known stellar mechanisms are unable to explain, pushing towards further observing and modeling efforts.